The Nonlinear Geometry of Banach Spaces - Kalton, Nigel J. (Revista Matemática Complutense, 2008)
We survey some of the recent developments in the nonlinear theory of Banach spaces, with emphasis on problems of Lipschitz and uniform homeomorphism and uniform and coarse embeddings of metric spaces.